THE ANALYSIS OF EXISTENTIAL PRESUPPOSITION IN THE SLOGAN OF “Y.O.U” THE SIMPLICITY LIPS - Novia Elisa Putri (Fakultas Bahasa & Sastra Universitas Wijaya Putra, 2022)
This research investigated existential presupposition in the Slogan of Y.O.U the Simplicity lips products. The research refered to describe the data that was gotten through the website advertisement. The purposes of this research were (1) finding the functions of existential presupposition in the slogan and (2) finding the factors on how the consumers were interested in the product through the slogans. In the analysis of the data, the writer used descriptive qualitative method. The method was suitable to interpret the problems which were raised by the writer. This research used the theory of Liping Ge to analyse the function of existential presupposition. And also used the theory of Denton to analyse the function of slogan.